Upaya Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran IPA Dengan Metode Demonstrasi di SMP Swasta Bunga Mawar Kota Gunungsitoli - Sepi Fita Sari Gea; Yesca Florensia Harefa; Agnes Renostini Harefa (Jurnal Ilmiah Wahana Pendidikan, 2023)
With a total of 31 students, this classroom action research (PTK) was conducted in class VII-A of Bunga Mawar Private Middle School, Gunungsitoli Bunga Mawar. The project, which was carried out in two cycles, aims to improve student learning outcomes in science learning using display techniques in class VII-A. The research data is qualitative in nature. At the end of each activity, student learning outcomes are obtained along with statistics on the teaching and learning process, results of qualitative data analysis on student observation sheets in cycles I and II. These results indicate that both the results of the final test of the action and the results of the first and second cycle of observations on the activities of students and teachers have increased. This shows that class VII-A students of Bunga Mawar Private Middle School, Gunungsitoli City, can obtain better learning outcomes when using a demonstration approach.